El régimen de suelo cómo instrumento de regulación del desarrollo urbano - Mendoza Castillo, Augusto (2025)
This article reviews the relationship between property ownership and urban development through urban regulation, most specifically the land regime, which is the way in which private property participates in urban development through the management of its development rights and its contributions to urban services. It analyzes the conceptual bases for the generation of urban regulation, that is, the relationship between property and the city and how its development conditions, the scope of the former. It is precisely the land regime that regulates the conditions in which private property is related to the city and contributes to its well-being and participates in the conditions of land development. This relationship allows the generation of land for the location of urban services. The two dimensions of the land regime are analyzed: classification and land qualification and how these relate to urban management through public investment and administrative acts.